2021
DOI: 10.1155/2021/9641846
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction and Dysmetabolic Syndrome: The Need for Enhanced Thyrovigilance Strategies

Abstract: Thyroid dysfunction (TD) is common in metabolic disorders such as diabetes mellitus (DM), cardiovascular disease (CVD), obesity, dyslipidemia, hyperuricemia, kidney and liver dysfunctions, and polycystic ovary syndrome (PCOS). Subclinical hypothyroidism (SHypo) worsens glycemic control in patients with DM, and these patients, especially those with Type-1DM, have higher prevalence of TD. Both TD and DM increase CVD risk. Even minor alteration in thyroid hormone (TH) levels can alter cardiovascular function. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 95 publications
3
18
0
2
Order By: Relevance
“…The incidence of SCH in the study population (31.1%) was consistent with the results of other studies [ 13 ], while the incidence of circulating ATA (12%) and AIT (4.4%) was slightly lower [ 14 , 17 ], which may be due to the characteristics of the study population and the diagnostic criteria used. The study confirmed that TSH values > 2.5 corresponding to SCH were associated with the occurrence of significant metabolic disturbances, which was in line with the majority [ 13 , 24 , 25 , 35 ], but not all [ 36 , 37 ], of previous scientific reports, and the strongest relationship was found for hyperlipidemia and insulin resistance [ 38 ]. Interestingly, the coexistence of ATA in the subpopulation with TSH > 2.5 (AIT) did not seem to additionally affect the values of metabolic parameters and the effect of elevated TSH levels was even greater in the absence of ATA, which, however, requires further research and verification.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The incidence of SCH in the study population (31.1%) was consistent with the results of other studies [ 13 ], while the incidence of circulating ATA (12%) and AIT (4.4%) was slightly lower [ 14 , 17 ], which may be due to the characteristics of the study population and the diagnostic criteria used. The study confirmed that TSH values > 2.5 corresponding to SCH were associated with the occurrence of significant metabolic disturbances, which was in line with the majority [ 13 , 24 , 25 , 35 ], but not all [ 36 , 37 ], of previous scientific reports, and the strongest relationship was found for hyperlipidemia and insulin resistance [ 38 ]. Interestingly, the coexistence of ATA in the subpopulation with TSH > 2.5 (AIT) did not seem to additionally affect the values of metabolic parameters and the effect of elevated TSH levels was even greater in the absence of ATA, which, however, requires further research and verification.…”
Section: Discussionsupporting
confidence: 86%
“…The coexistence of AIT with PCOS may be associated with an even greater risk of metabolic syndrome and infertility [ 22 , 23 ]. Complications pertain not only to overt hypothyroidism, but also SCH [ 24 , 25 ] and the presence of circulating anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-TG) antibodies [ 26 ]. However, not all research results are consistent in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PCOS can only be diagnosed after hypothyroidism has been ruled out. The relationship between insulin resistance and hypothyroidism has been studied for decades; however, the in uence of SCH on clinical and metabolic parameters has not been su ciently investigated in the setting of PCOS [13][14][15]. Thyroid hormones are involved in the metabolism of various substances in the body and may regulate gonadal development and female reproductive endocrine function through the hypothalamic-pituitary-ovarian axis.…”
Section: Discussionmentioning
confidence: 99%
“…Гормони щитоподібної залози є регуляторами клітинного розвитку, росту та обміну речовин у ссавців [24] та контролюють ряд метаболічних процесів у клітинах, пов'язаних з анаболізмом або катаболізмом макромолекул, включаючи вуглеводи, білки, ліпіди [11]. Дисбаланс рівнів тиреоїдних гормонів в організмі повʼязаний із множинними хронічними захворюваннями, включаючи цукровий діабет, серцево-судинні захворювання та печінкові розлади [7].…”
Section: вступunclassified